Childhood Trauma, Sleep Quality, and Maladaptive Coping Strategies: Understanding Adolescent Mental Health Challenges and Developing Effective Interventions - Alumdalu, Suci Alumdalu; Nurhasanah; Larasati, Wikan Putri; Nuradhi, Mohamad Abdilah (Sinergi International Journal of Psychology, 2024)
Adolescent mental health is increasingly recognized as a critical public health concern, with childhood trauma, sleep quality, and mental health disorders playing significant roles in shaping psychosocial well-being. This study employs a qualitative approach through in-depth interviews with adolescents and mental health professionals to explore the interconnections among adverse childhood experiences (ACEs), sleep disturbances, anxiety, depression, self-harm behaviors, and smoking. Thematic analysis reveals that childhood trauma is a major predictor of mental health disorders, leading to increased social withdrawal and maladaptive coping strategies. Sleep disturbances further aggravate emotional dysregulation, reinforcing cycles of anxiety and depressive symptoms. Additionally, adolescents engage in self-harm and smoking as mechanisms for temporary relief from psychological distress. Mental health professionals emphasize the need for evidence-based interventions such as cognitive behavioral therapy (CBT), dialectical behavior therapy (DBT), and school-based mental health programs. The findings highlight the urgent need for holistic, multi-sectoral interventions integrating family, educational institutions, and healthcare systems to support adolescent mental health. Future research should focus on the long-term effects of interventions and the potential of digital mental health solutions in mitigating adolescent distress. These insights contribute to the ongoing discourse on improving adolescent mental health policies and intervention frameworks.